If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3z + -2)(3 + z) = 0 Reorder the terms: (-2 + 3z)(3 + z) = 0 Multiply (-2 + 3z) * (3 + z) (-2(3 + z) + 3z * (3 + z)) = 0 ((3 * -2 + z * -2) + 3z * (3 + z)) = 0 ((-6 + -2z) + 3z * (3 + z)) = 0 (-6 + -2z + (3 * 3z + z * 3z)) = 0 (-6 + -2z + (9z + 3z2)) = 0 Combine like terms: -2z + 9z = 7z (-6 + 7z + 3z2) = 0 Solving -6 + 7z + 3z2 = 0 Solving for variable 'z'. Factor a trinomial. (-3 + -1z)(2 + -3z) = 0Subproblem 1
Set the factor '(-3 + -1z)' equal to zero and attempt to solve: Simplifying -3 + -1z = 0 Solving -3 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1z = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1z = 0 + 3 -1z = 0 + 3 Combine like terms: 0 + 3 = 3 -1z = 3 Divide each side by '-1'. z = -3 Simplifying z = -3Subproblem 2
Set the factor '(2 + -3z)' equal to zero and attempt to solve: Simplifying 2 + -3z = 0 Solving 2 + -3z = 0 Move all terms containing z to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3z = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3z = 0 + -2 -3z = 0 + -2 Combine like terms: 0 + -2 = -2 -3z = -2 Divide each side by '-3'. z = 0.6666666667 Simplifying z = 0.6666666667Solution
z = {-3, 0.6666666667}
| x^2+8x+6=25 | | 2x+5=4x+11 | | (lnx)(9x^8)= | | 4/3*x=7/12*x | | 5w^4-5w=0 | | 8m-(5+6m)= | | 5.9=5x+1.8 | | 25+5=8 | | x/2+4x/3=2x-1.5 | | log(4x+5)=log(x+5)+log(3) | | 3560+15x=c | | (n-4)(n-7)=0 | | 7x-2/-4=-10 | | Y-2.4=9 | | 4x^3-280x^2+4900=4x^3-200x^2+2500x | | 6m-(9+2m)= | | 8x+(5x+12)=90 | | 6(x-7.6)=8.4 | | 4x^3-200x^2+2500x=4x^3-280x+4900x | | r^2=-28 | | -21x=-108 | | 7x+6.73=4x+10 | | V/11=4/5 | | 113=6x-5(2x-13) | | 4x^3-280x+4900x=4x^3-200x+2500x | | (3x+60)=180 | | 2(3y-1)-x=0 | | 7.2a+5.54=-15.34 | | 2(3x+2)+2(4x-5)=22 | | 7.6x=-62.32 | | 6-y+1+4y=43 | | X-6=2.64 |